2013
DOI: 10.1111/adj.12018
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related changes in maxillary and mandibular cortical bone thickness in relation to temporary anchorage device placement

Abstract: Background: The aim of this study was to investigate the correlation between alveolar bone cortical thickness (ABCT) and age in the maxillae and mandible in humans. This information could then be translated into clinical application with temporary anchorage devices (TADs) in orthdontics. Methods: Samples comprised 82 post-mortem CT datasets (41 males and 41 females) aged between 11 to 50 years, and were divided into five different age groups and gender. Alveolar ABCT was measured in the labial/buccal and palat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
16
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
9
16
2
1
Order By: Relevance
“…Although Momin MA reported no gender-specific difference in anatomic risk of lingual plate fracture27, our data is partially supported by Sathapana’s findings that considerable difference of lingual bone thickness is observed in the retromolar region in men and women, and cortical bone increases more with age in women than in men33. However, we can’t rule out the other possibility to account for this gender difference, for example sample size, selection bias as well as measurement difference.…”
Section: Discussionsupporting
confidence: 61%
“…Although Momin MA reported no gender-specific difference in anatomic risk of lingual plate fracture27, our data is partially supported by Sathapana’s findings that considerable difference of lingual bone thickness is observed in the retromolar region in men and women, and cortical bone increases more with age in women than in men33. However, we can’t rule out the other possibility to account for this gender difference, for example sample size, selection bias as well as measurement difference.…”
Section: Discussionsupporting
confidence: 61%
“…Regarding the BCB thickness, the median values of the measurements showed values from 0.9 to 3 mm, depending on the level, sex, and tooth analyzed. Previous studies analyzing the BCB of the same region found thickness values similar to the present study (Jin et al, 2012;Sathapana et al, 2013;Zekry et al, 2014;Khumsarn et al, 2016). The comparison of the BCB thickness of the maxillary premolar teeth at the five levels analyzed showed that the highest thicknesses occurred at the apical region (MA) in both sexes and in both premolars.…”
Section: Discussionsupporting
confidence: 86%
“…Sathapana et al examined age-related changes in mandibular buccal bone thickness in 82 CT images and reported no statistically significant difference according to age group (33). In contrast, Swasty et al observed a significant difference in bone thickness between the 10-19-year-old group and those aged 20 years and older.…”
Section: Discussionmentioning
confidence: 99%